A new species of Palaemonella Dana, 1852, (Crustacea: Decapoda; Pontoniinae) from the Red Sea - Bruce, A. J. (Zootaxa, 2008)
A new species of the pontoniine shrimp genus Palaemonella Dana, 1852, from the Red Sea is described and illustrated. Found from 519–544m; this is the greatest depth from which this genus has so far been reported. It is a species of the Indo-West Pacific P. dolichodactylus species complex, to the taxa of which a key is provided.